2015
DOI: 10.1016/j.ceb.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Membrane contact sites, gateways for lipid homeostasis

Abstract: Maintaining the proper lipid composition of cellular membranes is critical for numerous cellular processes but mechanisms of membrane lipid homeostasis are not well understood. There is growing evidence that membrane contact sites (MCSs), regions where two organelles come in close proximity to one another, play major roles in the regulation of intracellular lipid composition and distribution. MCSs are thought to mediate the exchange of lipids and signals between organelles. In this review, we discuss how lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
117
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 46 publications
0
117
0
Order By: Relevance
“…The Ca 2+ -dependent role of E-Syts in the formation of MCSs between the ER and the plasma membrane, coupled with the proposed role for E-Syts in lipid transfer at these sites, suggests a function for localized Ca 2+ signals in establishing sites of lipid transfer. Ca 2+ exchange at ER -mitochondria MCSs, as discussed, is well established but MAMs have more recently been implicated in phospholipid transfer (reviewed in [29,61]), with transfer of phosphatidylserine (PS) from the ER to the mitochondria at MCSs recently demonstrated in yeast [28]. Finally, the role of oxysterol binding proteins in the formation of ER MCSs with the endocytic pathway suggests a role for these contacts in sterol transfer.…”
Section: Discussionmentioning
confidence: 95%
“…The Ca 2+ -dependent role of E-Syts in the formation of MCSs between the ER and the plasma membrane, coupled with the proposed role for E-Syts in lipid transfer at these sites, suggests a function for localized Ca 2+ signals in establishing sites of lipid transfer. Ca 2+ exchange at ER -mitochondria MCSs, as discussed, is well established but MAMs have more recently been implicated in phospholipid transfer (reviewed in [29,61]), with transfer of phosphatidylserine (PS) from the ER to the mitochondria at MCSs recently demonstrated in yeast [28]. Finally, the role of oxysterol binding proteins in the formation of ER MCSs with the endocytic pathway suggests a role for these contacts in sterol transfer.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequent studies have demonstrated that the ER interacts via tethering proteins with all other membranous organelles of the cell, and have identified a variety of functions for these contacts (7)(8)(9)(10)(11)(12). One major function is exchange of lipids between bilayers via lipid-transfer proteins (11,12,(21)(22)(23)(24). The occurrence of this mode of lipid transfer between membranes, which is independent of vesicular transport and membrane fusion, was first described in the late 1960s (25).…”
mentioning
confidence: 99%
“…aintenance of the unique lipid composition of different eukaryotic cell membranes requires a concerted regulation of lipid synthesis and transport via vesicular trafficking and nonvesicular lipid transfer (1)(2)(3). Most lipids in the cell are synthesized in the endoplasmic reticulum (ER) or taken up from the outside for degradation and reutilization via the endo-lysosomal system.…”
mentioning
confidence: 99%